Nanospectroscopy of single quantum dots with local strain control using a phase-change mask. (14th July 2017) - Saiki, Toshiharu; Shintani, Toshimichi; Kuwahara, Masashi; Regreny, Philippe; Gendry, Michel
Abstract: Herein, we describe a new technique that allows high-sensitivity near-field imaging spectroscopic analysis of individual quantum constituents in semiconductors. This method employs an optical mask composed of a phase-change material (PCM) and operates at optical telecommunication wavelengths. Superior collection efficiency and spatial resolution are achieved by using an amorphous nanoaperture as a result of the extreme optical contrast between the PCM in amorphous and crystalline phases at visible wavelengths and the good near-infrared transparency of this material. Fine tuning of quantum dot (QD) emission levels via localized strain as a result of the increase in volume of the PCM upon amorphization has also been demonstrated. Both red and blue shifts of the energy levels were predicted to occur beneath the flat and edge regions of the amorphous mask, respectively, using finite element simulations. The viability of localized strain tuning as an approach to nanospectroscopy employing phase changes was confirmed by measurements of the photoluminescence of individual InAs/InP QDs. In addition, the emission levels of two neighboring QDs were matched based on modifying the shift magnitudes and directions via careful adjustment of the indenter size and position.